Hubungan Motivasi Belajar Dengan Hasil Belajar Siswa Kelas V SDN 4 Simpang Teritip - Muhamad Imam Agus Faizal; Maulina Hendrik; Vika Martahayu (Universitas Muhammadiyah Bangka Belitung, 2023)
This research was motivated by the low learning motivation of fifth grade students in exploring education, and there were some participants who had an average cognitive aspect score (knowledge) on the basis of the minimum completeness criteria (KKM). This research aims to identify the relationship between learning motivation and learning outcomes of fifth grade students at SDN 4 Simpang Teritip. The type of research used is correlational quantitative, with a research position at SDN 4 Simpang Teritip. The research sample was all class V participants at SDN 4 Simpang Teritip, totaling 40 respondents. Collecting information using the questionnaire method and documentation. Information analysis was carried out by carrying out a correlation test using the Spearman rank correlation coefficient formula and a significance t test. The results of the analysis using Microsoft Excel and the SPSS application prove that there is a relationship with very high criteria for the relationship between learning motivation and learning outcomes, with scores of 0.906 and 0.909. The significance analysis of the relationship between learning motivation and learning outcomes also shows that t count > t table, with value 13.2722 > 1.6839, otherwise analysis using the SPSS application proves that the price is sig. 0.001 <0.05. Thus, it can be concluded that there is a significant relationship between learning motivation and learning outcomes of fifth grade students at SDN 4 Simpang Teritip.